SunfishÃ¢â¬â¢s (Mola spp.) Habitat Characteristics on their Appearance at Dive Tourism Depths in Nusa Penida Waters, Bali - Dewi SLKT; Mohammad Mukhlis Kamal; T Tarsidin; G Yulianto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
The sunfish or mola fish (Mola spp.) is one of marine tourismÃ¢â¬â¢ icon in Nusa Penida waters where they appear seasonally. This study was aimed to observe the habitat characteristics of mola fish at the depths of diving tourism where they are visible. The research was conducted from July to December 2019 using survey and descriptive methods to obtain information of mola fish animal linked to habitat conditions. On its appearance data on depths, temperatures, currents, and the presence of symbiotic fishes were observed directly assisted by dive center operators. By comparing the morphological characteristics shown photographically, it is assumed that mola fish in study area is composed by two species, M. alexandrini and M. mola. The highest individual record was in September and decreasing along the incoming months. Mola fish prefers calm deeper water with lower temperatures coincides with the presence of cleaning reef fishes.ÃÂ